Refracting “tools for conviviality” through the lived experience of machine translation in higher education - Johnson, Mike (Proceedings of the International Conference on Networked Learning, 2026)
This short paper is work-in-progress towards a fuller treatment of a study that adopts a phenomenology of practice approach to analyse the lived experience of machine translation (MT) in higher education, in the context of a bilingual country, Cymru (Wales, UK). The 2021 revised definition of networked learning replaced ‘digital’ with ‘convivial technology’ to state what NL is for, linking with Illichian ideas and thus better reflect the field’s historic commitment to critical pedagogy and emancipatory education. MT, as manifest through Web and mobile applications such as Google Translate, is briefly discussed and considered for its conviviality, in helping students overcome language barriers that are especially acute for non-native Saesneg (English) speakers. However, current instantiations of MT, such as Google Translate, may clumsily confound, rather than facilitate, attempts to obtain useable translation and thus comprehension when mobilised in use. With its Cymru/Cymraeg (Welsh) context, this paper adds a postcolonial aspect as the Welsh Government aims to support the survival of our native language, requiring all educational service providers inside and into Cymru not to treat Cymraeg any less favourably than Saesneg. The Welsh Government expects technology, MT especially, to play a key part in enabling the use of Cymraeg in formal settings, whether for written or spoken Cymraeg. As MT technologies, and their applications, advance, developers advertise gadgets that seemingly dissolve language barriers. Some scientists argue that effective MT would benefit indigenous scientific communities by allowing them to work in their native languages. This could accentuate digital divides, since new technology adoption is skewed in favour of the more financially privileged sections of society. Furthermore, translation and linguistics scholars argue that human translators achieve more than the exchange of equivalent words. With its focus on lived meanings, it is proposed that phenomenology can help to disclose insights into the ways or extent to which MT is a convivial technology. Van Manen’s phenomenology of practice approach operationalises core phenomenological concepts and method, and the work begun by framing a personal anecdote and reflection: a lecturer, lacking confidence in Cymraeg, tries to use Google Translate to humanise an email with a line of Cymraeg whilst on the move. Despite the intent, instrumental use of machine translation may be anticonvivial. Further areas for analysis are briefly proposed.